A Generalization of the Annulus Formula for the Relative Extremal Function - Lewandowski, Arkadiusz (MATHEMATICA SCANDINAVICA, 2014)
The main result of this paper is an annulus formula for the relative extremal function in the context of Stein spaces (Theorem 1.1). It has an application in the theory of extensions of holomorphic functions defined on generalized crosses in products of Stein spaces (Theorem 4.6).